PELATIHAN PENULISAN KARYA ILMIAH MENGGUNAKAN APLIKASI MENDELEY BAGI MAHASISWA TINGKAT AKHIR - Anwar Lubis; Ismi Irfiyanti Fachruddin; Sakinah Amir; Syamsuriah; Andi Hardianti (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
Scientific writing is an essential skill for final-year students, particularly in completing their undergraduate thesis and developing sustainable academic competencies. However, many students still face challenges in managing references and compiling bibliographies systematically. This community service activity aimed to enhance the skills of final-year students from the D4 Culinary Arts Program at Universitas Negeri Makassar in utilizing Mendeley as a reference management tool. The training was conducted through interactive lectures and hands-on practice sessions, involving 9 participants and held at the Laboratory of the Department of Family Welfare Education. Post-training evaluations indicated that most participants reached the level of “competent” to “able to mentor peers” in various skills, including account creation, software installation, integration with Microsoft Word, reference entry, automatic citation, and formatting of reference styles. There was a significant improvement in participants’ mastery of Mendeley's core features following the training. Although a few participants still experienced difficulty in adjusting citation styles, overall, the activity successfully increased students’ preparedness in scientific writing. This training is recommended for replication across other study programs as a strategic effort to strengthen digital academic literacy and improve the quality of student scientific writing within higher education institutions.